Web-based guided self-help cognitive behavioral therapy–enhanced versus treatment as usual for binge-eating disorder: a randomized controlled trial protocol - van Beers, Ella; Melisse, Bernou; de Jonge, Margo; Peen, Jaap; van den Berg, Elske; de Beurs, Edwin (Frontiers in Psychiatry, 2024)
Binge-eating disorder (BED) is a psychiatric disorder characterized by recurrent episodes of eating a large amount of food in a discrete period of time while experiencing a loss of control. Cognitive behavioral therapy-enhanced (CBT-E) is a recommended treatment for binge-eating disorder and is typically offered through 20 sessions. Although binge-eating disorder is highly responsive to CBT-E, the cost of treating these patients is high. Therefore, it is crucial to evaluate the efficacy of low-intensity and low-cost treatments for binge-eating disorder that can be offered as a first line of treatment and be widely disseminated. The proposed noninferiority randomized controlled trial aims to determine the efficacy of web-based guided self-help CBT-E compared to treatment-as-usual CBT-E. Guided self-help will be based on a self-help program to stop binge eating, will be shorter in duration and lower intensity, and will require fewer therapist hours. Patients with binge-eating disorder (N = 180) will be randomly assigned to receive guided self-help or treatment-as-usual. Assessments will take place at baseline, mid-treatment, at the end of treatment, and at 20- and 40-weeks post-treatment. Treatment efficacy will be measured by examining the reduction in binge-eating days in the previous 28 days between baseline and the end of treatment between groups, with a noninferiority margin (Δ) of 1 binge-eating day. Secondary outcomes will include full remission, body shape dissatisfaction, therapeutic alliance, clinical impairment, health-related quality of life, attrition, and an economic evaluation to assess cost-effectiveness and cost-utility. The moderators examined will be baseline scores, demographic variables, and body mass index. It is expected that guided self-help is noninferior in efficacy compared to treatment-as-usual. The proposed study will be the first to directly compare the efficacy and economically evaluate a low-intensity and low-cost binge-eating disorder treatment compared to treatment-as-usual. If guided self-help is noninferior to treatment-as-usual in efficacy, it can be widely disseminated and used as a first line of treatment for patients with binge-eating disorder. The Dutch trial register number is R21.016. The study has been approved by the Medical Research Ethics Committees United on May 25th, 2021, case number NL76368.100.21.